APLIKASI PEMESANAN PADA TOKO SABLON BAJU MENGGUNAKAN METODE RAPID APLICATION DEVELOPMENT - Sugeng, Jonny Kurniawan; Ikrimach, Ikrimach (Politeknik Bisnis Indonesia, 2024)
In today's digital era, advancements in information technology have had a significant impact on various sectors, including the business world.